Restricting Veto Use In Humanitarian Crises: Urgency For Un Charter Amendment - Panggabean, Frans Julian (AL-MANHAJ: Jurnal Hukum dan Pranata Sosial Islam, 2025)
This study examines the need to impose legal limitations on the use of veto power to reinforce the principle of sovereign equality under Article 2(1) of the United Nations Charter. It focuses on the absolute nature of the veto exercised by the permanent members of the United Nations Security Council, which remains legally unrestricted due to the absence of clearly defined legal standards regulating its exercise. In practice, this unrestricted authority has repeatedly obstructed humanitarian action and contributed to institutional paralysis during humanitarian crises. Using a normative juridical method with a conceptual and doctrinal approach, this research analyzes debates on veto power, the amendment procedure under Article 108 of the Charter, and the development of soft-law initiatives, including the Responsibility to Protect, the ACT Group's Code of Conduct, and the French–Mexican initiative. The findings suggest that absolute veto power fosters structural inequality among member states and erodes the legitimacy and effectiveness of the United Nations. The study concludes that a targeted amendment to the UN Charter, restricting the use of vetoes in clearly defined humanitarian crises, is both normatively justified and legally feasible within the existing constitutional framework of the United Nations.